Oxytocin and vasopressin: the social networking buttons of the body - Amrit Krishna Mitra (AIMS Molecular Science, 2021)
Neurotransmitters play the role of electrochemical signalling molecules which are essential for suitable brain functioning. Their dysfunction causes several mental and health disorders. Neurotransmitters are present at a very low concentration in the nervous system and they are mixed with many other biochemical molecules. The precise detection and nursing of these molecules are pretty decisive in brain studies. This mini-review portrays the research on oxytocin and vasopressin as an exemplar for exploring the social neuroscience as the subject of social neuroscience has decisively explored the complex territory between perception and action. These neuropeptides, oxytocin and vasopressin are evolutionarily extremely conserved mediators in order to regulate the complex social cognition and behaviour. They play significant role in social interactions, in maternal care and closeness, development of general trust and cooperation, controlling of labor and breastfeeding, regulation of blood pressure, social recognition, sexual behaviours and response to stress. They find applications for several treatment approaches in mental disorders in the form of autism, borderline personality disorder, social anxiety disorder and schizophrenia.